Ranking regular seasons in the NBA`s Modern Era using grey relational analysis - Pradhan, S. (Journal of Sports Analytics, 2018)
In the last few decades, the sports world has seen the precipitous rise of data-driven player analysis methods across many professional sports. In light of these advents to the field, the current paper offers a novel application of a multi-criteria classification scheme developed within the scholarly literature, that being: grey relational analysis (GRA), to the milieu of professional sports. Specifically, this technique is utilized in the context of the National Basketball Association (NBA) to rank regular seasons during the Modern Era (i.e., since the 1979-80 season, after the merger between the NBA and ABA) through the use of a constellation of statistics. A sample of 100 seasons initially classified by player efficiency rating (PER) were examined using GRA. Findings from the present study illustrate that Stephen Curry`s recent MVP campaign during the 2015-16 season for the Golden State Warriors was the top ranked overall regular season out of those sampled in the Modern Era. The use of GRA is compared to current popular indicators for player evaluation and efficiency. Future directions and implications for professional sports are discussed.